2002
DOI: 10.1103/physrevb.66.104407
|View full text |Cite
|
Sign up to set email alerts
|

Polarized neutron diffraction and Mössbauer spectral study of short-range magnetic correlations in the ferrimagnetic layered compounds(PPh4)[<

Abstract: 3 ͔ between 10 and 30 K of broad sextets and doublets in the Mössbauer spectra and the paramagnetic scattering observed in the polarized neutron measurements indicate the coexistence of spin-correlated and spin-uncorrelated regions in the layers of this compound. The polarized neutron scattering profiles and the Mössbauer spectra yield the magnetic exchange correlation length and lifetime, respectively, and the combined results are best understood in terms of layers composed of random frozen, but exchange corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…The isomer shift ( IS ) and the quadrupole splitting ( QS ) of the spectrum A at 200 K for ( n -C n H 2n+1 ) 4 N[Fe II Fe III (dto) 3 ](n = 3-6) are quite similar to those ( IS = 0.33 mm/s, QS = 0.35 mm/s at 196 K) of the 57 Fe Mössbauer spectrum for the Fe III ( S = 1/2) site in KBa[Fe III (dto) 3 ]·3H 2 O [56], where the Fe III site is coordinated by six S atoms. On the other hand, the IS and QS of the spectrum B at 200 K are quite similar to those ( IS = 1.235 mm/s, QS = 1.42 mm/s at 190 K) of the 57 Fe Mössbauer spectrum for the Fe II ( S = 2) site in ( n -C 4 H 9 ) 4 N[Fe II Fe III (ox) 3 ](ox = oxalato) [57], where the Fe II site is coordinated by six O atoms. Therefore, it is concluded that the Fe II ( S = 2) and Fe III ( S = 1/2) sites in ( n -C n H 2n+1 ) 4 N[Fe II Fe III (dto) 3 ](n = 3-6) are coordinated by six O atoms and six S atoms, respectively.…”
Section: A[feiifeiii(dto)3] (A = (N-cnh2n+1)4n Spiropyran; Dto = mentioning
confidence: 68%
See 2 more Smart Citations
“…The isomer shift ( IS ) and the quadrupole splitting ( QS ) of the spectrum A at 200 K for ( n -C n H 2n+1 ) 4 N[Fe II Fe III (dto) 3 ](n = 3-6) are quite similar to those ( IS = 0.33 mm/s, QS = 0.35 mm/s at 196 K) of the 57 Fe Mössbauer spectrum for the Fe III ( S = 1/2) site in KBa[Fe III (dto) 3 ]·3H 2 O [56], where the Fe III site is coordinated by six S atoms. On the other hand, the IS and QS of the spectrum B at 200 K are quite similar to those ( IS = 1.235 mm/s, QS = 1.42 mm/s at 190 K) of the 57 Fe Mössbauer spectrum for the Fe II ( S = 2) site in ( n -C 4 H 9 ) 4 N[Fe II Fe III (ox) 3 ](ox = oxalato) [57], where the Fe II site is coordinated by six O atoms. Therefore, it is concluded that the Fe II ( S = 2) and Fe III ( S = 1/2) sites in ( n -C n H 2n+1 ) 4 N[Fe II Fe III (dto) 3 ](n = 3-6) are coordinated by six O atoms and six S atoms, respectively.…”
Section: A[feiifeiii(dto)3] (A = (N-cnh2n+1)4n Spiropyran; Dto = mentioning
confidence: 68%
“…The IS and QS of the spectrum C for n = 3 and 4 are similar to those ( IS = 0.325 mm/s, QS = 0.39 mm/s) of the Fe II ( S = 0) site in [Fe II (bipy) 3 ](ClO 4 ) 2 (bipy = 2,2’-bipyridine) [58]. On the other hand, the IS and QS of the spectrum D for n = 3 and 4 are similar to those ( IS = 0.486, QS = 0.64 at 90 K) of the 57 Fe Mössbauer spectrum for the Fe III ( S = 5/2) site in ( n -C 4 H 9 ) 4 N [Fe II Fe III (ox) 3 ] [57]. …”
Section: A[feiifeiii(dto)3] (A = (N-cnh2n+1)4n Spiropyran; Dto = mentioning
confidence: 68%
See 1 more Smart Citation
“…At 45 K, the spectrum consists of a quadrupole doublet broadened by paramagnetic relaxation and characterized by an isomer shift of δ = 1.198 mm s −1 , and a quadrupole splitting of ΔE Q = 2.695 mm s −1 , which is consistent with high-spin Fe(II) centers. [52] Regarding the entire temperature range of the measurement, the doublets are well developed above 30 K, while the presence of closely connected asymmetric sextets occurs upon cooling below 25 K, which may indicate a long-or shortrange magnetic ordering or a slow relaxation on the Mössbauer timescale. [52]…”
Section: Fe Mössbauer Spectroscopymentioning
confidence: 88%
“…[52] Regarding the entire temperature range of the measurement, the doublets are well developed above 30 K, while the presence of closely connected asymmetric sextets occurs upon cooling below 25 K, which may indicate a long-or shortrange magnetic ordering or a slow relaxation on the Mössbauer timescale. [52]…”
Section: Fe Mössbauer Spectroscopymentioning
confidence: 88%